Poet - Acuna, (Tilde) Arbeen Regalado (Review of Women's Studies, 2023)
The artwork "poet" on the preceding page is a tribute to Nobel Laureate Wislawa Szymborska of Poland. She was awarded "for poetry that with ironic precision allows the historical and biological context to come to light in fragments of human reality." The portrait "poet" simplified into lines Syzmborska's photograph that appeared in the cover of "Here" (her posthumous poetry collection), to characterize her succinct articulation of timeless and contemporary issues. Below is a Filipino adaptation of her three poems from "Here" (2012).